Facile preparation of antibacterial MOF‐fabric systems for functional protective wearables. (14th June 2021) - Teo, Wei Liang; Liu, Jiawei; Zhou, Weiqiang; Zhao, Yanli
Abstract: Metal‐organic frameworks (MOFs) have shown numerous potentials as promising materials to address real‐world problems. However, their practical utilization in commercial products was largely limited by the lack of downstream processing methodologies to transform MOF powders into functional products. In this study, a commercially viable solution for the general synthesis of MOF‐fabric composites was introduced. On account of coordination bonding between poly(acrylic acid) and MOF substrates, MOF powders securely adhered onto the surface of fabric materials via a drip cast method to give MOF‐fabric composites easily. This strategy can be applied to different MOF types, as well as a wide variety of fabric materials. The prepared materials showed excellent bacterial killing efficacy attributed to the embedded HKUST‐1 MOF. In light of the recent coronavirus disease 2019 pandemic, this methodology could enable the large‐scale fabrication of essential MOF‐based personal protective wearables (e.g., clothing and masks) for use by healthcare professionals. Abstract : By using poly(acrylic acid) as a binder, a general and efficient methodology to firmly coat metal‐organic framework (MOF) powder onto fabric materials is described. Among all MOF‐based composites synthesized by this method, HKUST‐1 infused cloth and masks possess superior antibacterial properties, which are useful as materials for protective wearables in healthcare applications.